Effectiveness of a Multimodal Therapeutic Approach for Disorganization Symptoms in Hebephrenic Schizophrenia: A Case Report - Affan Tsaqif Taufiqurrahman; Winaryani Winaryani; Hafid Algristian (Indonesian Scientific Publication, 2026)
Hebephrenic schizophrenia, or disorganized-type schizophrenia, represents one of the most disabling and treatment-resistant subtypes of psychotic disorders, marked by disorganized thinking, affect, and behavior. These symptoms often persist despite standard pharmacological treatment and are associated with poor cognitive and social functioning. This case report explores the effectiveness of an integrated multimodal therapeutic approach that combines pharmacological, cognitive-behavioral, and metabolic strategies in managing a young woman with chronic hebephrenic schizophrenia. The patient, a 23-year-old female with a six-year illness duration and history of medication nonadherence, was treated with aripiprazole 15 mg/day (dopamine D2 partial agonist), trifluoperazine 5 mg/day (full D2 antagonist), folic acid 1 mg/day, and vitamin B6 100 mg/day. Cognitive Behavioral Therapy (CBT) and family psychoeducation were conducted twice weekly for three weeks. After treatment, she demonstrated measurable improvement, including a 1-point reduction in conceptual disorganization and a 2-point improvement in blunted affect (PANSS-R), alongside qualitative gains in coping with auditory hallucinations and affective responsiveness. These results suggest that synergistic modulation of dopaminergic circuits, cognitive restructuring, and metabolic support may yield short-term benefits for patients with treatment-resistant disorganization symptoms. Further longitudinal studies are warranted to evaluate long-term outcomes and neurobiological mechanisms.